2020
DOI: 10.1155/2020/4075792
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Structural Valve Deterioration after Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis

Abstract: Background. Transcatheter aortic valve replacement (TAVR), widely used as an alternative therapy in patients with severe aortic stenosis, is expected to be offered to low-risk patents with a longer life expectancy. The durability of transcatheter aortic valve is becoming of increasing importance. Method. PubMed, Embase, and Cochrane CENTRAL from the inception to March 2020 were systematically screened for studies reporting on structural valve deterioration (SVD) in TAVR patients. Incidence of SVD was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The incidence of moderate or severe SVD is ∼8.97% at 5 years after TAVI, with no significant differences in the risk of developing SVD between TAVI and SAVR at the 5-year mark. 5 Notably, self-expanding TAVI had a significantly larger EOA and lower mAVPG in echocardiograms than balloon-expandable TAV and SAVR (1.84 ± 0.54 vs. 1.51 ± 0.49 vs. 1.39 ± 0.45, P < 0.01; 7.42 ± 3.60 vs. 11.61 ± 6.65 vs. 11.33 ± 5.39, P < 0.01). 6 However, reports are lacking on the long-term procedural outcomes of TAVI in haemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of moderate or severe SVD is ∼8.97% at 5 years after TAVI, with no significant differences in the risk of developing SVD between TAVI and SAVR at the 5-year mark. 5 Notably, self-expanding TAVI had a significantly larger EOA and lower mAVPG in echocardiograms than balloon-expandable TAV and SAVR (1.84 ± 0.54 vs. 1.51 ± 0.49 vs. 1.39 ± 0.45, P < 0.01; 7.42 ± 3.60 vs. 11.61 ± 6.65 vs. 11.33 ± 5.39, P < 0.01). 6 However, reports are lacking on the long-term procedural outcomes of TAVI in haemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with a high life expectancy are usually offered surgery instead of TAVR due to concerns about durability, a significant number of TAVR patients still experience these complications during their lifetime. For example, a meta‐analysis found that the pooled incidence of structural valve deterioration in TAVR patients at 1 year was 4.93% 88 . Given that the indications for TAVR are being expanded further to low‐risk patients with a longer life expectancy, 13,14 bioprosthetic valve failure could soon become a much bigger issue.…”
Section: Postprocedural Imaging and Complicationsmentioning
confidence: 99%
“…For example, a meta‐analysis found that the pooled incidence of structural valve deterioration in TAVR patients at 1 year was 4.93%. 88 Given that the indications for TAVR are being expanded further to low‐risk patients with a longer life expectancy, 13 , 14 bioprosthetic valve failure could soon become a much bigger issue.…”
Section: Postprocedural Imaging and Complicationsmentioning
confidence: 99%